PENGARUH KUALITAS LAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN PESERTA PEMEGANG KARTU JKN KIS BPJS KESEHATAN (Studi peserta pemegang kartu JKN KIS pada BPJS Kesehatan di Kantor Cabang Semarang) - Radevi Avi Yulianti, 15.05.51.0193; Sutejo, Bambang (Students' Journal of Economic and Management, 2019)
This study aims to examine and analyze the influence of service quality and trust in participant satisfaction. This research was conducted at the BPJS Semarang Branch Office. The population in this study were 2,726,198 JKN KIS BPJS Health card holders at the Semarang Branch Office. The number of samples used in this study were 100 people. Sampling using Slovin formula with purposive sampling technique. The data analysis technique used is validity test, reliability test, multiple regression analysis, F test, determination test and hypothesis test to test service quality variables and confidence in the satisfaction of JKN KIS BPJS Health Card holders Semarang Branch Office satisfaction. The results of the study show that service quality has a positive and significant effect on the satisfaction of participants of the JKN KIS BPJS Health Card holders Semarang Branch Office. Trust has a positive and significant effect on satisfaction of participants of the JKN KIS BPJS Health Card holders Semarang Branch Office.